IMPLEMENTASI PEER GROUP SUPPORT DENGAN METODE STORYTELLING TERHADAP SELF PROTECTION SKILLS DAN KNOWLEDGE: STRATEGI PENCEGAHAN KEKERASAN SEKSUAL PADA ANAK - Nurul Laili; Ro'isah Ro'isah; Ainul Yaqin Salam (Jurnal Keperawatan dan Kesehatan Masyarakat Cendekia Utama, 2025)
Background: The incidence of violence against children has been increasing, with the majority of cases involving sexual abuse. Most victims are girls, and the perpetrators are predominantly individuals close to the child. This phenomenon is closely linked to children’s low levels of self-protection skills and knowledge. Survey data indicate that 98% of elementary school students have inadequate self-protection skills and limited understanding of sexual abuse. Based on these findings, it is essential to provide appropriate interventions to enhance children’s self-protection skills and knowledge. This study aims to examine the implementation of Peer Group Support through the storytelling method on children’s Self-Protection Skills and Knowledge. Methods: This study employed a quasi-experimental design with a non-equivalent group pre-test and post-test approach. A total of 160 respondents participated, consisting of 80 in the control group and 80 in the experimental group. Data were collected using the Self-Protection Model Questionnaire and The Children’s Knowledge of Abuse Questionnaire. Data analysis was conducted using the Wilcoxon test. Results: The results showed a p-value < 0.05 (0.000 < 0.05), indicating a significant effect of the Peer Group Support intervention with the storytelling method on improving children’s self-protection skills and knowledge in the experimental group. Conclusion: The combination of Peer Group Support and the storytelling method can serve as an effective strategy in child sexual abuse prevention programs, as it is easy to implement, participatory, child-friendly, and promotes children’s confidence in taking protective actions. The implementation of Peer Group Support through storytelling has been proven to enhance children’s self-protection skills and knowledge as a preventive measure against sexual violence.